How best to determine causative pathogens of pneumonia. Issue 1 (December 2016) - Murdoch, David
Abstract The biggest recent development in pneumonia diagnostics has been the increased availability and use of nucleic acid detection assays, although this change has brought with it new challenges about the interpretation of positive results. Recognition of the existence of the lung microbiome has challenged the traditional views of pneumonia pathogenesis and may provide the opportunity for new diagnostic tools that are focused on more than just detection of specific known pathogens.